ANALISIS KUALITAS PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN SEMARANG - Dwi Handyan Prasetyo; Mochammad Mustam (Journal of Public Policy and Management Review, 2018)
"Pro investor" investment into the program in the era of the reign of Joko Widodo to propel the influx of investors, so the Government should have already prepared in terms of services especially services permissions. Problems faced by DPMPTSP Semarang is the lack of human resources. This study aims to describe the quality of service analysis about licensing in DPMPTSP Regency Semarang. Research methods used in this research is descriptive qualitative research methods. The theory being used, namely the principles of quality service according to PERMENPANRB No. 14 Year 2017 which include: requirements, mechanisms, Systems and procedures, the time of completion, cost/rates, product specification type of service, managing competencies, Managing behavior, handling complaints, feedback, and suggestions, and infrastructure. The results showed the quality of service permissions on DPMPTSP Semarang meets nine quality service principles, it is apparent from the community satisfaction received from services provided in DPMPTSP Regency Semarang. Some shortcomings occurred on the principle of quality service burupa lack of socialization, the procedure is less effective and efficient for the employees, the lack of human resources, and a lack of infrastructure and facilities for employees in DPMPTSP Regency Semarang. Recommendations, the need for dissemination of dissemination to the Community requirements, simplification of the procedure of licensing for Ministry employees, the addition of a clerk at DPMPTSP Semarang, and renewal of infrastructure and facilities for the employees in the DPMPTSP Regency Semarang.